the effect of value clarification technique model on the understanding of historical values of grade XI students at SMAN 1 tapung hulu: Pengaruh Model Value Clarification Technique (VCT) Terhadap Pemahaman Nilai-nilai Sejarah Kelas XI di SMAN 1 Tapung Hulu - Sri Rahmadani; Isjoni; Asril (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study is about the influence of the Value Clarification Technique (VCT) learning model in improving the understanding of historical values ​​in class XI IPAS 1 and IPAS 2 at SMA Negeri 1 Tapung Hulu. The problems in this study are how the value clarification technique model influences the understanding of historical values ​​of class XI at SMAN 1 Tapung Hulu, how the application of the value clarification technique learning model is to the understanding of historical values ​​of class XI at SMAN 1 Tapung Hulu and whether there is an influence of the Value Clarification Technique (VCT) learning model in improving historical awareness in class XI IPAS students at SMA Negeri 1 Tapung Hulu. This study uses a comparative method with a Quasi-Experimental Designs design in the form of a Non-Equivalent Control Group which will create two experimental groups that are not selected through Random. Where this study aims to improve students' historical awareness through the application of the Value Clarification Technique (VCT) learning model. The instruments used are field notes and tests (pre-test and post-test). Based on the results of the study, it shows that the use of the Value Clarification Technique (VCT) learning model can increase historical awareness, this is indicated by the t-value of 10.779 and the sig. value of 0.000. So, the sig. value of 0.000 <0.05, then Ho is rejected and Ha is accepted. This means that there is an influence on the History Subject, by using the Value Clarification Technique (VCT) model on increasing the historical awareness of class XI IPAS students at SMA Negeri 1 Tapung Hulu.